Preparation of electrolytic polishing liquid for PCB metallographic section for observing original morphology of copper-plated layer and method for observing original morphology of copper-plated layer
By using new electrolytic polishing liquid and electrochemical electrolytic polishing technology, the problems of mechanical stress and micro-etching liquid treatment in the observation of copper plating layers in the prior art are solved, and high-quality, residual stress-free polishing surface and true morphology observation are achieved, reducing cost and operational complexity.
Patent Information
- Application Number
- CN202211540476.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-02
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-12-02
AI Technical Summary
In the prior art, when observing the original morphology of the copper-plated layer of the printed circuit board, there is a problem that mechanical stress influence and the difference between surface etching after micro-etching liquid treatment, resulting in interference in the observation information or damage to the morphology.
A new electrolytic polishing liquid is adopted, which consists of analyzing pure phosphoric acid, ethanol, isopropanol, distilled water and hexylglycol. The electrolytic polishing is performed by electrochemical methods, removing the mechanical strain layer and smoothing the surface.
A high-quality polished surface without residual stress influence is achieved, and the true original morphology of the copper plating layer is clearly observed, reducing costs and simplifying the operation process.
Smart Images

Figure CN116005239B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an electrolytic polishing liquid for preparing a PCB metallographic slice for observing the original morphology of a copper-plated layer, a method for preparing a PCB metallographic slice for observing the original morphology of a copper-plated layer, and a method for observing the original morphology of a copper-plated layer. Technical Background
[0002] In the production process of printed circuit boards (PCBs), the role of the metallization process is to achieve signal interconnection between layers. As printed circuit boards are now developing towards high density and high precision, the quality requirements for metallized copper plating are becoming higher and higher. In PCB industrial production, the quality of copper plating is usually confirmed by metallographic sectioning.
[0003] The existing metallographic section preparation method generally obtains the information of the cross section of the copper plating layer through a series of means such as sampling, mounting, grinding, polishing, and display (electron microscope observation). The sampling and grinding process will cause the sample to deform and leave rough wear marks on the surface, and polishing is to eliminate the wear marks left by the previous sample preparation process. The traditional polishing method is to apply polishing particles on a rotating disc covered with soft fabric. When the surface of the metallographic section to be polished is close to it, a flat surface is obtained by mechanical grinding. Although the surface obtained in this way is flat, the information obtained by observation will be disturbed due to the mechanical stress on the surface during preparation. Micro-etching liquid (generally hydrogen peroxide + ammonia system) is commonly used in the PCB industry to remove the interference layer caused by mechanical stress in sample preparation, but the etching difference of the copper layer surface treated with micro-etching liquid is large, which will also destroy the original morphology of the sample surface. In this way, the key information required for observation may be concealed in the subsequent observation and analysis using a scanning electron microscope, or "false" surface morphology information that is disturbed may be obtained. In conventional metallographic preparation methods, the grain boundaries are strongly attacked, and even a stripe boundary similar to interlayer separation is formed between the interfaces of the copper plating layers. However, after FIB (focused ion beam) inspection, it was found that there was no interlayer separation defect at this location, see 5a, Figure 5b and Figure 5c FIB is a technology that uses metal ions to accelerate and focus through an electric field to exfoliate atoms from the sample surface. It can achieve micro-nanoscale processing of the sample surface, and thus clearly reveal the original morphology of the sample surface.
[0004] The electrolytic polishing process is to use the sample as the anode and another selected metal as the cathode, put the sample into the electrolytic polishing liquid, connect direct current, and under a certain electrochemical mechanism, selectively dissolve the protrusions on the sample surface, so that the sample surface becomes flat and smooth. Due to the different physical and chemical properties of the samples themselves, the electrolytic polishing liquid and working parameters for different samples also need to be selected in a targeted manner. At present, the composition of the electrolytic polishing liquid for electrolytic copper / electroplated copper samples generally includes phosphoric acid and water (see CN110514503A), or includes phosphoric acid, water, ethanol, etc. (see CN110699749A). These existing electrolytic polishing liquids have been proven to be feasible for electrolytic polishing of printed circuit boards with large areas of pure copper as substrates. However, in the field of microscopic analysis of PCBs, such as PCB metallographic sections, since the substrate of the PCB is a composite material (copper, resin, glass fiber, etc.), the influence of various material combinations makes the electrolysis rate of the surface of the PCB metallographic section inconsistent. After being treated with the existing electrolytic polishing method, the originally flat sample surface becomes uneven (see Figure 9a and 9b ), with the glass fiber as the center, the surrounding copper dissolution rate is too fast. Limited by the above situation, in the current PCB industry, accurate and reliable information on the original surface morphology of the plated (copper) layer needs to be obtained by FIB means. However, FIB equipment and consumables are expensive, sample preparation requires professional technicians and sample preparation is time-consuming. To prepare a high-quality 10 micron x 10 micron cross-section as an observation position, it generally requires spraying a conductive layer, adjusting the alignment, plating a Pt film, ion beam stripping and other processes, which takes about 30 minutes and is costly. Summary of the invention
[0005] In view of the above-mentioned defects existing in the process of observing the original morphology of the copper-plated layer of a printed circuit board in the prior art, an object of the present invention is to provide an electrolytic polishing solution for preparing a PCB metallographic section for observing the original morphology of the copper-plated layer. The electrolytic polishing solution comprises the following components by weight: 15-50% analytical pure phosphoric acid, 15-50% ethanol, 2-10% isopropanol, 25-65% distilled water, and 0.05-2% hexanediol.
[0006] The substrate of the above-mentioned PCB metallographic slice is made of copper, or made of a composite material.
[0007] The above-mentioned hexanediol may be selected from 1,2-hexanediol and / or 1,6-hexanediol.
[0008] In some preferred embodiments of the present invention, the electrolytic polishing solution comprises the following components: 18-40% analytical pure phosphoric acid, 18-40% ethanol, 3-8% isopropanol, 30-50% distilled water, and 0.1-1% hexanediol.
[0009] In some more preferred embodiments of the present invention, the electrolytic polishing solution comprises the following components: 20-30% analytical pure phosphoric acid, 20-30% ethanol, 4-6% isopropanol, 35-45% distilled water, and 0.15-0.5% hexanediol.
[0010] In a preferred embodiment of the present invention, the electrolytic polishing liquid is composed of the following components: 24% analytical pure phosphoric acid, 24% ethanol, 5% isopropanol, 46.8% distilled water, and 0.2% 1,6-hexanediol. The substrate of the PCB metallographic section is made of copper or a composite material.
[0011] Another object of the present invention is to provide a method for preparing a PCB metallographic section for observing the original morphology of a copper-plated layer, the method comprising the following steps:
[0012] (1) preparing the electrolytic polishing solution: uniformly mixing analytical pure phosphoric acid, ethanol, isopropanol, distilled water and hexylene glycol to obtain the electrolytic polishing solution;
[0013] (2) Preparation of PCB metallographic sections: Preparation of PCB metallographic sections by sampling, mounting, grinding, mechanical polishing and electrolytic polishing;
[0014] The electrolytic polishing process is to immerse the mechanically polished sample in the electrolytic polishing solution prepared in step (1) and polish it for 2-4 seconds at a voltage of 4-6V.
[0015] In some preferred embodiments of the present invention, the grinding is to grind the sample on a grinder successively using metallographic sandpaper of different numbers until the surface is smooth.
[0016] In some preferred embodiments of the present invention, the grinding is performed by sequentially using 1200 mesh, 2400 mesh and 4000 mesh metallographic sandpaper to grind the sample.
[0017] In some preferred embodiments of the present invention, the mechanical polishing is performed on a polishing disk using a polishing cloth and aluminum oxide polishing particles.
[0018] In some preferred embodiments of the present invention, the aluminum oxide polishing particles are 1 micron in size.
[0019] Another aspect of the present invention provides a method for observing the original morphology of a copper plating layer, the method comprising:
[0020] (1) preparing a PCB metallographic slice using the above-mentioned PCB metallographic slice preparation method, wherein the substrate of the PCB metallographic slice is made of copper or a composite material;
[0021] (2) The original morphology of the copper-plated layer of the PCB metallographic section was observed using a scanning electron microscope.
[0022] The technical solution of the present invention has the following advantages and effects:
[0023] The electrolytic polishing liquid for preparing PCB metallographic slices for observing the original morphology of the copper-plated layer of the present invention can smooth the surface of the PCB metallographic slice while avoiding the influence of mechanical stress on the surface of the PCB metallographic slice, thereby obtaining a high-quality polished surface without residual stress, so that the true original morphology of the copper-plated layer can be observed through a scanning electron microscope. Moreover, whether the substrate of the PCB metallographic slice is made of copper or a composite material, a good effect can be obtained.
[0024] By observing the surface of the PCB metallographic slice prepared by the present invention using a scanning electron microscope, the copper grain morphology and the interface between different coatings can be clearly and truly observed, which is used to analyze failed samples of inner layer interconnect defects, analyze early failure samples of interconnect stress experiments, study the physical properties of coatings, or control product quality.
[0025] The electrolytic polishing liquid used in the present invention is composed of phosphoric acid, ethanol, isopropanol, deionized water and hexylene glycol. Each component is safe and harmless, has a simple proportion, is easy to handle and has low cost.
[0026] Compared with the existing reliable FIB observation of the original morphology of the copper-plated layer, the method for observing the original morphology of the copper-plated layer of the present invention has a short sample processing time, simple processing steps and easy operation.
[0027] Instruction Manual
[0028] Figure 1 It is a schematic diagram of the structure of the electrolytic polishing equipment used in the present invention, wherein the cathode and the sample (anode) are immersed in the electrolyte together, and under certain working parameters, the surface of the sample is selectively dissolved, thereby making the surface flat and smooth.
[0029] Figure 2 It is an electrolytic polishing device actually constructed by the present invention, in which the sample (anode) is clamped by stainless steel tweezers and connected to a DC power supply through a wire, and a pure copper plate is used as the cathode, which is connected to a DC power supply through a wire.
[0030] Figure 3 It is a backscattered electron image of the copper-plated layer surface after sampling, mounting, grinding and mechanical polishing, and then treated with traditional micro-etching solution (the composition of the micro-etching solution is a mixture of hydrogen peroxide (mass concentration 30%) and ammonia water (mass concentration 35%) in a volume ratio of 1:1). From this figure, it can be seen that the interface between the copper-plated layer and the inner connecting copper layer is separated, but it is impossible to determine whether this position has failed.
[0031] Figure 4This is a backscattered electron image of the surface of the copper-plated layer after sampling, mounting, grinding, and mechanical polishing, and then electrolytically polishing using the electrolytic polishing solution of the present invention. From this image, the morphology of grains with different orientations can be observed.
[0032] Figure 5a , Figure 5b and Figure 5c The copper-plated layer photos were taken after ion cutting of the sample using the TESCAN LYRA3XMH focused ion beam system. The cutting position and Figure 3 , Figure 4 The results observed after treatment with the focused ion beam system are consistent with the phenomenon observed after electrolytic polishing using this method ( Figure 4 ), it can be seen that there is actually no separation between the copper plating layer and the inner layer. Figure 3 The separation phenomenon between the copper-plated layer and the inner layer observed in the figure is an illusion caused by the micro-etching solution (the composition of the micro-etching solution is a mixture of hydrogen peroxide (mass concentration 30%) and ammonia (mass concentration 35%) in a volume ratio of 1:1) treated on the copper layer during the traditional metallographic sectioning process.
[0033] Figure 6a The grain morphology of the copper-plated surface of the PCB metallographic section obtained by sampling, mounting, grinding, mechanical polishing and electrolytic polishing (using the electrolytic polishing solution of the present invention) of the printed circuit board after electroplating and without heat treatment is observed using a scanning electron microscope. Figure 6b The invention relates to the grain morphology observed by a scanning electron microscope on the surface of the copper-plated layer of a PCB metallographic slice obtained by sampling, mounting, grinding, mechanical polishing and electrolytic polishing (using the electrolytic polishing liquid of the present invention) of a printed circuit board after electroplating and heat treatment.
[0034] Figure 7 It is an image observed using a scanning electron microscope on the surface of a PCB metallographic slice obtained by sampling, mounting, grinding, mechanical polishing and electrolytic polishing (using the electrolytic polishing liquid of the present invention). From the image, the nano-scale thin layer of the chemical copper deposition layer can be clearly observed.
[0035] Figure 8a This is a backscattered electron image (5000x) of a PCB metallographic section obtained by sampling, mounting, grinding, mechanical polishing and electrolytic polishing (using the electrolytic polishing solution of the present invention). From this figure, it can be seen that the failure position of the sample and the crack runs through the entire coating. Figure 8bThis is a backscattered electron image (30000x) of a PCB metallographic section obtained by sampling, mounting, grinding, mechanical polishing and electrolytic polishing (using the electrolytic polishing liquid of the present invention). From this figure, it can be seen that the entire coating is composed of a three-layer structure.
[0036] Figure 9a The surface morphology (5000 times) was taken by scanning electron microscope after treatment with traditional electrolyte formula (phosphoric acid: water 7:1). Figure 9b The surface morphology (1000 times) was taken after being treated with the traditional electrolyte formula (phosphoric acid: water 7:1). From the photos taken, it can be seen that the surface treated with the traditional electrolyte formula is uneven, making it difficult to achieve the ideal observation effect.
[0037] Fig.10a It is an image of the surface of a metallographic section of a printed circuit board (whose substrate is made of a composite material containing glass fiber) obtained by sampling, mounting, grinding, mechanical polishing and electrolytic polishing (using existing electrolytic polishing liquid, the composition of the electrolytic polishing liquid is phosphoric acid: water 7:1, 2.8V electrolytic polishing for 3s) observed using a scanning electron microscope. It can be seen from the figure that there is almost no polishing effect. Fig.10b It is an image of the surface of a metallographic section of a printed circuit board (whose substrate is made of a composite material containing glass fiber) obtained by sampling, mounting, grinding, mechanical polishing and electrolytic polishing (using existing electrolytic polishing liquid, the composition of the electrolytic polishing liquid is phosphoric acid: water 7:1, 5.0V electrolytic polishing for 3s) observed using a scanning electron microscope. It can be seen from the figure that it is difficult to distinguish the morphology of each grain.
[0038] Fig.11a This is a backscattered electron observation image of the copper surface of the sample to be analyzed collected by a scanning electron microscope. From the image, it can be seen that black particles can be observed scattered on the copper surface to be observed. The particles are found to be glass fiber fragments on the substrate. During the electrolytic polishing process, the copper layer of the circuit board is partially dissolved, while the resin and glass fiber parts in the substrate are not dissolved, and the remaining substrate forms a cliff-like morphology. Among them, the glass fiber is a relatively brittle material. After losing the wrapping and supporting effect of the surrounding copper layer, part of it is scattered on the copper surface below. Since the main components of glass fiber are oxygen (atomic number 8) and silicon (atomic number 14), the atomic number is smaller than that of copper (atomic number 29). In the observation of the backscattered electron image, the probability of backscattered electron excitation of the glass fiber part is much smaller than that of the copper surface part. The contrast of the backscattered electron image is determined by the number of backscattered electrons collected in each part of the image, so the black granular obstruction part is left in the observation image of the copper surface. Through the secondary electron image, the phenomenon of glass fiber shattering can be clearly observed, such as Fig.11bThe sample substrate in this example is relatively loose. This example shows that in the actual application of electrolytic polishing, in addition to correctly implementing the polishing steps, it is also very important to adjust the polishing parameters according to the characteristics of the sample. Referring to this example, appropriately reducing the polishing time can reduce the etching amount of copper to avoid excessive exposure and shedding of the substrate (refer to Example 5 below).
[0039] Fig.12a and Figure 12b The original morphology of the copper-plated layer on the surface of the copper-plated layer of the PCB metallographic section obtained by sampling, mounting, grinding, mechanical polishing and electrolytic polishing (using the electrolytic polishing liquid of the present invention) is observed using a scanning electron microscope. From this figure, it can be seen that the grain morphology of the coating has an abnormal parallel growth grain texture. DETAILED DESCRIPTION
[0040] The electrolytic polishing liquid for preparing PCB metallographic sections (the PCB metallographic sections are used to observe the original morphology of the copper-plated layer) comprises the following components: 15-50% of analytical pure phosphoric acid, 15-50% of ethanol, 2-10% of isopropanol, 25-65% of distilled water and 0.05-2% of hexanediol.
[0041] "Analytical pure phosphoric acid" is a commercially available phosphoric acid aqueous solution with a mass concentration of 85%. The role of phosphoric acid in the electrolytic polishing process is to form a sticky film layer on the copper surface. The diffusion flow is slower near the concave parts of the sample surface, and the film layer formed is thicker, while the film layer formed near the convex parts of the sample surface is thinner. The film has a large resistance, so the current density is large where the film is thin, and the current density is small where the film is thick. The current density is large in the convex parts of the sample surface, and the metal dissolves quickly in the electrolyte, while the concave parts dissolve slowly, so that the convex parts gradually become flat, and finally form a bright and smooth polished surface. The role of ethanol in the electrolytic polishing process is to dissolve the film layer and control its thickness within a suitable range. The main role of hexanediol in the electrolyte is 1. to stabilize the pH value in the solution 2. to control the etching rate of copper in the solution, so that the reaction rate on the entire polished surface is stable and consistent. The combination of ethanol, isopropanol and hexanediol can effectively control the rate of oxidation reaction on the copper surface during electrolytic polishing and reduce the surface roughness of the copper surface after etching.
[0042] The method for preparing a PCB metallographic section for observing the original morphology of a copper-plated layer of the present invention uses a novel electrolytic polishing liquid to electrochemically remove the mechanical strain layer on the surface of the PCB metallographic section, and then uses a scanning electron microscope to observe the original morphology of the copper-plated layer, so as to obtain original information of the cross section of the coating, such as the structure of the copper layer, the morphology of the grains, etc.
[0043] The preparation process of the PCB metallographic slice for observing the original morphology of the copper-plated layer of the present invention is: sampling, mounting, grinding, mechanical polishing, and electrolytic polishing. The sampling, mounting, grinding, and mechanical polishing processes are conventional methods for making (preparing) metallographic slices in the art. The processing object of the PCB metallographic slice method for observing the original morphology of the copper-plated layer of the present invention should be a surface prepared strictly in accordance with the metallographic preparation process, and thus it is described in order below.
[0044] First, sampling, mounting, grinding, and mechanical polishing are performed according to the conventional metallographic section preparation process. When mounting, the resin powder and curing agent should be prepared so that the prepared resin liquid is not too dense, so that there will be a large shrinkage when the resin liquid exotherms and solidifies, resulting in a gap between the mounting resin and the sample. The gap is not easy to remove after water seepage, which will affect the subsequent observation of the surface and increase the polishing area during electrolysis. You can consider using low-stress mounting resins such as Buehler's Epoxicure or Kulzer's Technovit 2000LC to improve the shrinkage gap problem after the resin powder and curing agent are mixed and heated. When mounting, conductive materials such as copper sheets that are exposed outside the slice can also be pre-embedded to facilitate anode connection during the subsequent electrolysis process. The purpose of mechanical polishing here is mainly to remove scratches left during the grinding process. The polished surface should have no scratches visible to the naked eye. Clean the metallographic section and blow it dry. If a powdered polishing agent such as aluminum oxide and silicon dioxide polishing particles are used, polishing particles are likely to remain on the sample surface. During the cleaning process, an ultrasonic cleaner can be used to clean for 1 minute to completely remove the polishing particles remaining on the surface. Then, an electrolytic polishing device is built, such as Figure 1 As shown, the cathode of the DC power supply is connected to the copper plate, and a conductive material such as a titanium plate that does not affect the electrolyte can also be selected. The anode of the DC power supply is connected to the stainless steel tweezers, and the surface of the copper layer exposed in the slice is clamped. If the conductive material is buried when the sample is mounted before, it can be directly clamped on the exposed part of the conductive material without damaging the surface of the copper layer. Figure 2 This is an actual electrode polishing device for the present invention. Finally, the power supply is turned on for electrolytic polishing, and the metallographic section is processed in the electrolytic polishing solution of the present invention at a voltage of 3.5V to 5.0V for 1 to 3 seconds. The section is cleaned with DI water and ethanol, and observed after drying.
[0045] In the field of PCB metallographic slice analysis, the conventional metallographic microetching method (chromic acid or ammonia-hydrogen peroxide chemical etching metallographic slice) treats the surface of the mechanically polished PCB metallographic slice, resulting in the destruction of the chemical copper deposition layer, which cannot be observed. However, the surface of the PCB metallographic slice sample prepared by the electrolytic polishing solution of the present invention is smooth (see Figure 4 ), without the illusion of conventional processing, the nano-thin layer of chemical copper deposition can be clearly observed (see Figure 7), reaching the sample level observed by FIB means.
[0046] In the field of PCB metallographic slice analysis, compared with the FIB preparation method, the method of preparing PCB metallographic slices for observing the original morphology of the copper-plated layer by using the electrolytic polishing liquid of the present invention through sampling, mounting, grinding, mechanical polishing and electrolytic polishing is low in cost, safe and simple to operate, and the preparation time can be greatly reduced. The method and equipment of the present invention for preparing PCB metallographic slices for observing the original morphology of the copper-plated layer mainly include a voltage stabilizer and a wire assembly, both of which are equipment that can be easily purchased on the market, and the operation of the method can be independently completed by a technician with a basic knowledge of metallographic analysis and chemical operation. The method of the present invention for preparing PCB metallographic slices for observing the original morphology of the copper-plated layer can complete the sample preparation in about 5 minutes, and the entire slice position to be observed can be processed at one time, without the need to prepare and process each observation position of the slice separately as in FIB.
[0047] Existing electrolytic polishing liquids, for example, the electrolytic polishing liquid disclosed in CN110514503A is a mixture of H3PO4 and deionized water, which is not suitable for preparing PCB metallographic sections for observing the original morphology of the copper-plated layer. In order to more intuitively illustrate this problem, the inventors herein compare the electrolytic polishing liquid of the present invention with the electrolytic polishing liquid disclosed in Chinese application number CN110514503A. These electrolytic polishing liquids are used for electrolytic polishing, wherein the production process of the PCB metallographic section is as above, including sampling, mounting, grinding, mechanical polishing and electrolytic polishing, and the results are shown in Table 1 below. It can be seen from the results in Table 1 that after polishing with the electrolytic polishing liquid disclosed in CN110514503A, it is difficult to obtain a good surface morphology even after repeatedly optimizing the working parameters, while after polishing with the electrolytic polishing liquid of the present invention, a high-quality surface morphology of the copper-plated layer can be directly obtained.
[0048] Table 1
[0049]
[0050]
[0051] During the preparation of PCB metallographic sections, the mechanism of electrolytic polishing is as follows: the electrolyte near the anode surface of the sample forms a viscous film of uneven thickness on the sample along with the uneven surface of the sample. The diffusion flow is slower near the concave part of the sample surface, and the film layer formed is thicker, while the film layer formed near the convex part of the sample surface is thinner. The reason why the sample can be polished is closely related to this film. The resistance of the film is large, so the current density is large where the film is thin, and the current density is small where the film is thick. The current density is large in the convex part of the sample surface, and the metal dissolves quickly in the electrolyte, while the concave part dissolves slowly, so that the convex part gradually becomes flat, and finally forms a bright and smooth polished surface.
[0052] The meanings of the abbreviations in the present invention are shown in Table 1 below.
[0053] Table 1
[0054]
[0055]
[0056] The present invention is further described below in conjunction with specific examples. It should be understood that the following examples are only used to provide the best practice mode of the present invention for further detailed description and should not be interpreted as limiting the scope of the present invention. The experimental methods in the following examples where specific conditions are not specified are usually carried out according to conventional operating methods and conditions, or according to the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are calculated by weight. The scanning electron microscope used in the following examples is: Manufacturer: FEI, Model: Inspect F50.
[0057] Example 1 Analysis of customer's suspected ICD failure samples
[0058] Use the following steps to prepare PCB metallographic sections:
[0059] (1) Sampling: Use a cutter to cut a 20mm x 10mm sample from the target area on the PCB. When sampling, keep the edge of the target through hole 3mm away from the cutting edge to avoid mechanical stress during cutting. Carefully grind the removed slice on 1200-grit silicon carbide metallographic sandpaper to the edge of the through hole.
[0060] (2) Mounting: Place the sample in DI water for ultrasonic cleaning to remove oil and resin residue on the surface. After drying the sample, use a plastic tripod to fix the sample vertically. Place the fixed sample into the rubber mold with tweezers. Mix metallographic glue powder (WESTEL 40-1100-010) and metallographic curing agent (WESTEL 40-1100-008) in a ratio of 2:1 and stir evenly. Pour the mixed acrylic solution into the rubber mold until it is flush, and gently lift the sample with tweezers to drive out the air attached to its surface. Let the mold stand until it is completely cured, and squeeze the rubber mold to demold the cured metallographic slice.
[0061] (3) Grinding: Use 600-mesh metallographic sandpaper on a grinder to grind the back of the slice flat and remove sharp edges for easy gripping. Use 1200-mesh metallographic sandpaper to grind the section to be observed on the slice. During the grinding process, maintain an appropriate rotation speed and pressure to prevent overly rough scratches on the surface. At the same time, add appropriate water flow for flushing to cool the grinding surface and remove the debris generated during the grinding process. After grinding to the section position to be observed, clean the surface with clean water. Replace with 2400-mesh metallographic sandpaper for fine grinding. During this process, pay attention to keeping 90° perpendicular to the grinding direction of the previous step and maintain appropriate pressure. After this step is completed, replace with 4000-mesh metallographic sandpaper for further fine grinding. Note the same points as above.
[0062] (4) Mechanical polishing: Use long-pile velvet cloth and 1-micron aluminum oxide polishing particles. Wet the velvet cloth with clean water and evenly spread the polishing particles on the polishing disc. Hold the slice and polish it in the opposite direction of the polishing disc. Pay attention to the polishing surface until it is bright, flat, and has no visible scratches.
[0063] (5) Electrolytic polishing: Ultrasonic clean the sample after mechanical polishing with DI water for 1 minute to remove the polishing particles and residues attached to it, and then blow dry the sample. Pour 240ml phosphoric acid, 240ml ethanol, 50ml isopropanol, and 2ml 1,2-hexanediol into a beaker, dilute to 1L with DI water, and stir evenly. Connect the sample to the anode of a DC power supply and the copper sheet to the cathode, place the two levels horizontally opposite each other, and immerse them in the electrolytic polishing solution. Set the voltage to 5V, remove it after 3 seconds of power on, clean it with DI water and ethanol in sequence, and blow dry it.
[0064] (6) Observation: Connect the slices with conductive tape, fix them to the base, and place them into the sample chamber of a scanning electron microscope for observation. The backscattered electron image obtained can be found in Figure 4 ,From this figure, we can see that the interface between the copper plating layer and the inner layer is well connected, and it can be judged that the sample is qualified.
[0065] The same position was observed by FIB (FIB preparation method refers to JY / T 0583-2020, the FIB system used is TESCAN LYRA3XMH, and the results are shown in Figure 5a , Figure 5b and Figure 5c It can be seen that the phenomenon observed by FIB is consistent with the phenomenon observed by scanning electron microscope after electrolytic polishing of PCB metallographic slices using the electrolytic polishing solution of the present invention.
[0066] After the above samples were sampled, mounted, ground, and mechanically polished, a cotton swab was dipped in a small amount of micro-etching solution (a mixture of hydrogen peroxide (mass concentration of 30%) and ammonia (mass concentration of 35%) in a volume ratio of 1:1) and gently wiped on the surface of the sample for 5 seconds (conventional mechanical polishing micro-etching method). The backscattered electron image observed under a scanning electron microscope is shown in Figure 2. Figure 3 ,From this figure, it can be seen that the interface of the copper plating layer and the inner layer copper layer is separated, but it is impossible to tell whether this position is failed.
[0067] Example 2 Analysis of Customer IST Early Failure Samples
[0068] The sample preparation process is the same as steps (1) to (5) in Example 1. In this example, the composition of the electrolytic polishing solution in step (5) is adjusted, specifically, 230 ml of phosphoric acid, 230 ml of ethanol, 70 ml of isopropanol, and 1.5 ml of 1,6-hexanediol are poured into a beaker, and the volume is adjusted to 1 L with DI water, and stirred evenly. The other steps and condition parameters remain unchanged.
[0069] After the PCB metallographic section is electrolytically polished by the electrolytic polishing solution of the present invention, the backscattered electron image observed under the scanning electron microscope is shown in FIG. Figure 8a and Figure 8b , Figure 8a The failure position of the sample is shown. The crack runs through the entire coating. Figure 8b The microstructure of the fracture is shown. From this figure, it can be seen that the entire coating is composed of a three-layer structure, and there are a large number of gaps at the interface between the primary copper plating layer (the rightmost side) and its outer layer. It can be seen that after electrolytic polishing the PCB metallographic section using the electrolytic polishing liquid of the present invention, the grain morphology of the copper plating layer can be clearly observed using a scanning electron microscope. The grains of the middle coating of the failed sample are loosely arranged and there are a large number of gaps, which causes the small cracks generated in the early stage of thermal fatigue to extend and spread through them, causing the entire coating to quickly break and fail.
[0070] Example 3: Impact of substrate shielding
[0071] When the sample to be analyzed in this embodiment was observed for the first time using a scanning electron microscope, it was found that the observation surface was blocked by black matter, such as Fig.11a As shown, further research found that the sample substrate may lose the support of the coating, and the glass fiber fragments fall to the surrounding coating, affecting the observation. This PCB sample was prepared into a PCB metallographic section by the steps (1) to (5) described in Example 1. During the preparation of the PCB metallographic section, the electrolysis time was reduced to 2s to reduce the amount of coating erosion. The composition and working parameters of the electrolytic polishing solution used in step (5) are as follows:
[0072] Electrolyte: 250ml phosphoric acid, 230ml ethanol, 60ml isopropanol, 1.8ml 1,6-hexanediol, 458.2ml DI water;
[0073] Working voltage: 5V
[0074] Electrolysis time: 2s
[0075] Using a scanning electron microscope to observe the metallographic section of the PCB, it was found that the occlusion of glass fiber fragments was eliminated, and the sample to be analyzed was qualified. Fig.11b .
[0076] From this example, we can see that in the actual application of electrolytic polishing, in addition to correctly implementing the polishing steps, it is also very important to adjust the polishing parameters according to the characteristics of the sample. Referring to this example, appropriately reducing the polishing time can reduce the amount of copper etching to avoid excessive exposure and shedding of the substrate.
[0077] Example 4 Study on Physical Properties of Coating
[0078] During the factory production process, it is often found that there are small corrosion holes on the surface of the copper plating, and this phenomenon can be improved after heat treatment under certain conditions. It is difficult to observe the difference between the morphology of the coating before and after heat treatment in visual observation and conventional metallographic analysis (refer to IPC-TM-6502.1.1). The steps and condition parameters for preparing PCB metallographic sections in Example 1 are used to prepare PCB metallographic sections before heat treatment and PCB metallographic sections after heat treatment, respectively. Then, using a scanning electron microscope, it can be observed that after the heat treatment of the coating, the originally small grains merge and grow, the fibrous crystals grow into a polygonal structure, and the multi-layered distinct coating structure begins to gradually unify. See Figure 6a and Figure 6b .
[0079] Example 5 Assisting in production quality control
[0080] The samples of the copper electroplating process in the factory were used to prepare the PCB metallographic sections according to steps (1) to (5) of Example 1. In step (5) of this example, the configuration of the electrolyte was adjusted. Specifically, 200 ml of phosphoric acid, 300 ml of ethanol, 40 ml of isopropanol, and 5 ml of 1,6-hexanediol were poured into a beaker, and the volume was adjusted to 1 L with DI water, and stirred evenly. The other steps and condition parameters remained unchanged.
[0081] The slices were connected with conductive tape, fixed to the base, and placed into the sample chamber of a scanning electron microscope for observation. It was found that the product coating grain morphology had an abnormal parallel growth grain texture (see Fig.12a and 12b ), based on experience, this texture may affect the reliability of the product. After communicating with the customer and conducting thermal shock tests, it was found that the coating fractured and failed. In the end, the hidden dangers of this batch of products were discovered in the early stage of the production process, avoiding the waste of subsequent production costs and the flow of products with reliability defects to downstream customers.
[0082] It should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An electrolytic polishing solution for preparing PCB metallographic sections for observing the original morphology of the copper-plated layer, characterized in that: The electrolytic polishing solution includes the following components by weight:
2. The electrolytic polishing liquid for preparing PCB metallographic sections for observing the original morphology of the copper-plated layer according to claim 1, characterized in that: The substrate of PCB metallographic section is made of copper or composite material.
3. The electrolytic polishing liquid for preparing PCB metallographic sections for observing the original morphology of the copper-plated layer according to claim 1 or 2, characterized in that: The hexanediol is selected from 1,2-hexanediol and / or 1,6-hexanediol.
4. The electrolytic polishing liquid for preparing a PCB metallographic section for observing the original morphology of the copper-plated layer according to claim 3, characterized in that: The electrolytic polishing solution includes the following components by weight:
5. The electrolytic polishing liquid for preparing PCB metallographic sections for observing the original morphology of the copper-plated layer according to claim 4, characterized in that: The electrolytic polishing solution includes the following components by weight:
6. An electrolytic polishing solution for preparing PCB metallographic sections for observing the original morphology of the copper-plated layer, characterized in that: The electrolytic polishing liquid is composed of the following components by weight: The substrate of the PCB metallographic slice is made of copper or a composite material.
7. A method for preparing a PCB metallographic section for observing the original morphology of a copper-plated layer, characterized in that: The preparation method comprises the following steps: (1) preparing the electrolytic polishing solution according to any one of claims 1 to 6: uniformly mixing analytical grade phosphoric acid, ethanol, isopropanol, distilled water and hexylene glycol to obtain the electrolytic polishing solution; (2) Preparation of PCB metallographic sections: sampling, mounting, grinding, mechanical polishing and electrolytic polishing, The electrolytic polishing process is to immerse the mechanically polished sample in the electrolytic polishing solution prepared in step (1) and polish it for 2-4 seconds at a voltage of 4-6V.
8. The preparation method according to claim 7, characterized in that: In step (2), the grinding is to grind the sample on a grinder successively using different numbers of metallographic sandpaper until the surface is smooth, and / or The mechanical polishing is performed on a polishing disk using a polishing cloth and aluminum oxide polishing particles.
9. A method for observing the original morphology of a copper plating layer, characterized in that: The method comprises: (1) Preparing a PCB metallographic slice using the preparation method according to any one of claims 7 to 8, wherein the substrate of the PCB metallographic slice is made of copper or a composite material; (2) The original morphology of the copper-plated layer of the PCB metallographic section was observed using a scanning electron microscope.
10. The method for observing the original morphology of the copper plating layer according to claim 9, characterized in that: Observing the original morphology of the copper plating layer is used to analyze the inner layer interconnection defect failure samples, analyze the early failure samples of the interconnection stress experiment, study the physical properties of the plating layer or control the product quality.
Citation Information
Patent Citations
Pure copper sample preparation method
CN110514503A
Method for preparing large-area continuous single-layer monocrystal graphene film
CN110699749A
Process for flattening diamond film by utilizing compound diamond-like carbon (DLC) film
CN101935825A
Polishing solution for printed circuit microsections and preparation method thereof
CN102746795A